Faktor-Faktor Yang Mempengaruhi Penerapan Good Agricultural Practices (GAP) Pada Perkebunan Kelapa Sawit di Indonesia : Kajian Literatur - Prameswari, Halissa Dwinta; Faisal, Faisal; Ananda, Muhammad Rizky; Sastrawan, Uding (CV Widina Media Utama, 2025)
This paper aims to analyze the factors that influence good agricultural practices on oil palm commodity plantations in Indonesia. This research employs a Systematic Literature Review (SLR) method. Based on the analysis of the outcomes from the implementation of good agricultural practices in oil palm plantations, it includes aspects such as technical preparation for cultivation, management of oil palm plantations, proper harvesting processes, the implementation of good sanitation to facilitate workers, and the benefits of applying good agricultural practices. The factors affecting good agricultural practices include the treatment of cultivation preparation such as land and water management, selection of superior seeds, fertilization systems, pruning techniques, and pest and disease control. The optimal implementation of these factors has been proven to enhance production yields and farm efficiency.ABSTRAKKajian literatur ini bertujuan untuk menganalisis faktor-faktor yang mempengaruhi praktik pertanian yang baik pada komoditas perkebunan kelapa sawit di Indonesia. Penelitian ini menggunakan pendekatan metode Systematic Literature Review (SLR). Berdasarkan analisis hasil dari penerapan praktik pertanian yang baik pada kebun kelapa sawit meliputi aspek teknis persiapan budidaya, pengelolaan kebun kelapa sawit, proses panen yang baik, penerapan sanitasi yang baik untuk memfasilitasi pekerja, dan manfaat dari penerapan praktik pertanian yang baik. Faktor-faktor yang mempengaruhi praktik pertanian yang baik meliputi perlakuan persiapan budidaya seperti pengelolaan lahan dan air, pemilihan bibit unggul, sistem pemupukan, teknik pemangkasan, serta pengendalian hama dan penyakit. Implementasi yang optimal dari faktor-faktor ini terbukti mampu meningkatkan hasil produksi dan efisiensi usaha tani.